Estereotipos científicos. Percepción del alumnado de un Centro de Adultos de Granada (España) - Serna Rosell, Cayetana; Vílchez González, José Miguel (Revista Científica, 2018)
Numerous studies have shown that social perception of Science is infused with naive visions and society transmitted stereotypes. Despite the large amount of research existing in this field, most of the studies that support the existence of Science stereotypes were carried out on children and youngsters and the majority of same took place in other countries. The present work aims to reflect the social perception of Science within a group of adult people residing in Granada, Spain, and this through the analysis of 88 drawings using the “Draw a scientist test” method. As a novelty, this work includes a pilot study with the purpose to get to know if it would be possible to change this Science stereotypic perception by using pictures. The results show a certain stereotyped image of the scientist, which is similarly shown in people of different ages, sex, origin or intellectual level. In addition, this image is resistant to change.